A correlation analysis on the postpartum anxiety disorder and influencing factors in puerperae with gestational diabetes mellitus - Zeng, Xun; Yan, Xiaofen; Yang, Yan; Peng, Zhangqing; Wei, Shiyao; Chen, Jinxia; Wu, Fengchun; Chen, Jiebing; Zhao, Ming; Luo, Chunqi (Frontiers in Endocrinology, 2023)
Objective The aim of this study is to discuss the postpartum anxiety disorder and influencing factors in puerperae with gestational diabetes mellitus (GDM) to provide a clinical basis for better early identification and intervention of adverse mood. Methods Convenient sampling method was adopted to investigate 205 pregnant women as the observation group and 201 normal healthy pregnant women in the same period as the control group. The self-rating anxiety scale (SAS) was used to investigate and observe the respondents, evaluate the postpartum anxiety status of patients with GDM, and analyze the related influencing factors. Statistical analysis of the data was performed using SAS 3.0 software. A proposed P < 0.05 was considered as statistically significant. Results Patients with GDM had a higher risk than normal maternal anxiety, related to years of education, triglycerides, 1-h postprandial blood glucose, and a history of induced abortion. Conclusion GDM can lead to the occurrence of postpartum anxiety, and the poor psychological state is not conducive to the maternal and infant health. Early identification and early intervention can reduce the harm caused by anxiety and promote the progress of maternal and infant health and clinical research.